If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying R(s + t) = st (s * R + t * R) = st (sR + tR) = st Solving sR + tR = st Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-1st' to each side of the equation. sR + -1st + tR = st + -1st Combine like terms: st + -1st = 0 sR + -1st + tR = 0 Add '-1tR' to each side of the equation. sR + -1st + tR + -1tR = 0 + -1tR Combine like terms: tR + -1tR = 0 sR + -1st + 0 = 0 + -1tR sR + -1st = 0 + -1tR Remove the zero: sR + -1st = -1tR Combine like terms: -1tR + tR = 0 sR + -1st + tR = 0 The solution to this equation could not be determined.
| 5(8a-b)-8(8b-4a)= | | 2(3r+5)-3(r-5)= | | -76+67= | | (8x-3)-(5x+6)=6 | | -4(2x)=5(7) | | 3b-5-12b-8= | | 6(w-4)=12 | | -7x^2-7x=0 | | 6x-10=2(x+3) | | 13=-5x+23 | | 2x+x+7=4x-4 | | 6+4n+3=9+3n | | 15-5(4x-7)=-70 | | -5(2p+4)-24=4(5p+4) | | (8x+4)= | | 5x-1=2(x-5) | | x^4-4096=0 | | 9-5n+3n=19-52 | | -46+7y+9=3(4y-2)-6 | | 15-5(4x+3y)= | | 6n-20=4n | | 2x^2-5xy+11xy+3= | | 4k-(2k-6)= | | 3(2y-4)-2(y+2)= | | 3x-20+3x-20=2x-4 | | 4b-3-7b-8= | | 3x+2x^2=54 | | T=d+pm | | 25a^2+80at+64t^2=1 | | 6x^5+14x-9x^4-21= | | 2p+15=9 | | 25a^2+80at+64t^2=0 |